2021
DOI: 10.1186/s13287-021-02495-3
|View full text |Cite
|
Sign up to set email alerts
|

A NOTCH1/LSD1/BMP2 co-regulatory network mediated by miR-137 negatively regulates osteogenesis of human adipose-derived stem cells

Abstract: Background MicroRNAs have been recognized as critical regulators for the osteoblastic lineage differentiation of human adipose-derived stem cells (hASCs). Previously, we have displayed that silencing of miR-137 enhances the osteoblastic differentiation potential of hASCs partly through the coordination of lysine-specific histone demethylase 1 (LSD1), bone morphogenetic protein 2 (BMP2), and mothers against decapentaplegic homolog 4 (SMAD4). However, still numerous molecules involved in the oste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Of note, MFAP5 activated Notch 1 signaling in certain tumors, promoting tumor invasion and migration (Chen et al 2020 ; Li et al 2019 ). Notch 1 signaling is also involved in osteogenesis (Díaz-Tocados et al 2017 ; Fan et al 2016 ; Fan et al 2021 ). However, the Notch 1 levels of the MFAP5 knockdown and control groups did not differ significantly (see Additional file 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, MFAP5 activated Notch 1 signaling in certain tumors, promoting tumor invasion and migration (Chen et al 2020 ; Li et al 2019 ). Notch 1 signaling is also involved in osteogenesis (Díaz-Tocados et al 2017 ; Fan et al 2016 ; Fan et al 2021 ). However, the Notch 1 levels of the MFAP5 knockdown and control groups did not differ significantly (see Additional file 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Notch1 is a target of miR-137, which acts as a regulator of Notch signaling in neurons. Consistent observations in human adipose cells have shown that miR-137 binds directly to the NOTCH1 3′UTR region and ultimately positively regulates HES1 (Shi et al, 2017;Fan et al, 2021). Recent evidence provides insight into the role of miR-137 in response to oxidative damage and neuroprotection with a proposed neuroprotector and anti-inflammatory role against chemical agents and artery occlusion (Y.…”
Section: Unfolded Protein Response (Upr) Is Disturbed In Szmentioning
confidence: 84%
“…The plasmids of negative control (NC), miR‐137 overexpression (miR‐137), miR‐137 knockdown (anti‐miR‐137), LGR4 shRNA (anti- LGR4 ) and RANKL shRNA (anti- RANKL ) were separately employed to generate the corresponding lentiviruses. The hASCs were transfected by respective lentiviruses as previously described ( Ma et al , 2020 ; Fan et al , 2021 ). After being immersed in the viral supernatant (multiplicity of infection = 100) with 5 mg/mL polybrene (Sigma-Aldrich) for 24 h, the cells were then selected by 1 μg/ml puromycin (Sigma-Aldrich) and cultured in fresh PM.…”
Section: Methodsmentioning
confidence: 99%
“…As an ideal stem cell source, human adipose-derived mesenchymal stem cells (hASCs) are widely used in bone tissue engineering due to their accessibility, multipotency and low immunogenicity ( Dinescu et al , 2021 ). MicroRNAs (miRNAs), a class of small non-coding RNAs ranging from 19-25 nucleotides in size, regulate protein-coding genes post-transcriptionally and play crucial roles in various biological activities, including the proliferation and osteogenic differentiation of hASCs ( Ranganathan and Sivasankar, 2014 ; Fan et al , 2021 ). It has been demonstrated that miR-137 acts as a key regulator in various kinds of malignancies ( Li et al , 2017 ; Liu et al , 2017 ; Qin et al , 2017 ; Luo et al , 2018 ; Zhang et al , 2018 ) and neural development ( Silber et al , 2008 ; Szulwach et al , 2010 ; Tarantino et al , 2010 ; Sun et al , 2011 ; Jiang et al ,2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation